The Woolwich Arsenal and Acadian Mines - Pryke, Kenneth (Scientia Canadensis, 2011)
In 1856 the Royal Arsenal undertook to locate a British source for high grade ore that would be suitable for purposes of ordnance. Early reports indicated that one of the irons being evaluated, an iron from Nova Scotia, was comparable to Swedish iron. Having adopted a rigid policy of modernization, the Arsenal insisted that all irons had to meet the standards established by the analytical chemists. When the Acadian iron was subsequently rejected, critics claimed that the chemists were promoting dogma, not science. The procedures being used by the chemists were certainly flawed, and the Arsenal project incident illustrated that at that time analytical chemistry had relatively little to offer the metal trades.